Solving 2nd Order Nonlinear Differential Equations Using Piecewise Analytic Method (Pendulum Equations) - Abassy, Tamer Ahmed (International Journal of Applied Mathematical Research, 2021)
In this paper, piecewise analytic method (PAM) is used for solving highly nonlinear 2nd Â order differential equation (pendulum equations) which is a big problem for engineers and scientists. PAM is used for showing the nonlinear dynamics of the solution with and without linearizion. The error and accuracy of the solution are controlled easily according to our needs.